2019
DOI: 10.3390/ani9090624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Aged Maize with Oxidized Fish Oil on Growth Performance, Antioxidant Capacity and Intestinal Health in Weaned Piglets

Abstract: Simple SummaryIn China, large quantities of maize are stored in grain depots for two years or more to mitigate the risk of natural disasters impacting feed supplies. However, it is unknown whether the use of long-term stored maize in diets will impair growth performance of piglets, and whether additional dietary oxidants would further exacerbate the effects. This study investigates the effects of dietary aged maize with the supplementation of different levels of oxidized fish oil on growth performance, nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The reduced EE digestibility in the present study is in accordance with Luo et al [39], which indicated 8% reduction in the apparent total tract digestibility of EE in weaned pigs consuming 3% oxidized (POV = 120.85 mEq kg −1 ) fish oil-based diets. Lindblom et al [26], similarly, documented 6% reduction of EE digestibility in growing pigs consuming soybean oil, which was heated at 90°C for 72 hrs.…”
Section: Discussionsupporting
confidence: 92%
“…The reduced EE digestibility in the present study is in accordance with Luo et al [39], which indicated 8% reduction in the apparent total tract digestibility of EE in weaned pigs consuming 3% oxidized (POV = 120.85 mEq kg −1 ) fish oil-based diets. Lindblom et al [26], similarly, documented 6% reduction of EE digestibility in growing pigs consuming soybean oil, which was heated at 90°C for 72 hrs.…”
Section: Discussionsupporting
confidence: 92%
“…66 Many of these studies have observed that feeding of LOPs can significantly diminish animal growth. [67][68][69][70][71][72] The findings of our study are generally consistent with these studies in the livestock agriculture field. However, the effects of LOPs on body weight in our study are modest compared to several above-mentioned studies.…”
Section: Discussionsupporting
confidence: 89%
“…117 In adult patients, Zhang et al observed that obese individuals have significantly higher abundances of members of the order Methanobacteriales than post-gastric bypass and normal individuals. 118 LOPs have become prevalent in human, 119 livestock [67][68][69][70][71][72] and pet 120 diets in the United States and other developed countries. With the exception of research in livestock agriculture field focusing on growth and meat quality, there is little research on the impact of dietary LOPs, especially as it relates to human or other animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the harmful effects of oxidized fish oil on breeding production have been widely reported [ 6 , 7 ]. In several experiments in poultry, mice, and piglets, the dietary addition of oxidized fish oil was found to exacerbate oxidative stress and damage in the organism by reducing antioxidant-related enzymes [ 8 , 9 , 10 ]. Therefore, oxidative stress models constructed by the dietary addition of oxidized fish oil have been used extensively in animal experiments.…”
Section: Introductionmentioning
confidence: 99%